1/r 的傅里叶变换

先做 $e^{-ar}/r$ 的傅里叶变换,再令 $a=0$,得 $1/r$ 的傅里叶变换。

$e^{-ar}/r$ 的傅里叶变换为

\begin{equation} \begin{split} \mathcal F[e^{-ar}/r]=&\int d^3\vec{r}\frac{e^{-ar}}{r}e^{-i\vec{q}\cdot\vec{r}}\\ =&\int_0^{\infty} \frac{e^{-ar}}{r}r^2dr\int_0^{\pi}\sin\theta e^{-iqr\cos\theta}d\theta\int_0^{2\pi}d\phi\\ =&2\pi\int_0^{\infty} \frac{e^{-ar}}{r}r^2dr\int_0^{\pi} e^{-iqr\cos\theta}d(-\cos\theta)\\ =&2\pi\int_0^{\infty} \frac{e^{-ar}}{r}\frac{1}{iqr}\left ( e^{iqr\cos\theta}-e^{-iqr\cos\theta} \right )r^2dr\\ =&\frac{4\pi}{q}\int_0^{\infty} e^{-ar}\sin (qr)dr\\ =&\frac{4\pi}{q}\mathrm{Im}\left [\int_0^{\infty} e^{-ar}e^{iqr}dr \right ]\\ =&\frac{4\pi}{q}\mathrm{Im}\left [\int_0^{\infty} e^{(iq-a)r}dr \right ]\\ =&\frac{4\pi}{q}\mathrm{Im}\left [ \frac{e^{(iq-a)r}}{iq-a} \right ]\left.\right|_0^{\infty}\\ =&-\frac{4\pi}{q}\frac{e^{-ar}[q\cos(qr)+a\sin(qr)]}{q^2+a^2}\left.\right|_0^{\infty}\\ =&\frac{4\pi}{q^2+a^2} \end{split} \label{FTa} \end{equation}

令 $a=0$,得 $\frac{1}{r}$ 的傅里叶变换:

\begin{equation}
\mathcal F\left[\frac{1}{r}\right]=\frac{4\pi}{q^2}
\label{FTa0}
\end{equation}

标签: 傅里叶变换

添加新评论

captcha
请输入验证码